Plasmon properties of multilayer albumin/gold hybrid nanoparticles - Flores, Constanza Yanel (2019)
Hybrid nanoparticles are mainly based on inorganic (metal, semiconductors) and organic (proteins, polymers) compounds. The inorganic compounds are metallic nanostructures with unique features such as localized surface plasmon resonance (LSPR) bands in the UV–visible-near IR spectral range. The LSPR frequency is extremely sensitive to small changes in the physicochemical environment surrounding NPs and is dependent on NP shape and size. Recently, we reported a novel preparation method of hybrid nanoparticles based on an Albumin multilayer coating of AuNPs, stabilized by radiation-induced crosslinking processes. With this method, we obtained core/shell nanoparticles composed by Au and albumins. The aim of this paper is the description of the plasmon properties of AuNPs and other core/shell gold/protein NPs prepared. UV–vis spectra were used to detect changes of the plasmon extinction of hybrid nanoparticles, in accordance to the Mie Theory. DLS and TEM measures were used to correlate the results obtained. UV–vis spectroscopy proved to be key to characterize protein layer through two parameters: thickness and refractive index. In conclusion, UV–vis spectroscopy can be a very useful quality control methodology to prepare hybrid Au/protein NPs.